THU0609-HPR RESPONSIVENESS OF THE DISABILITIES OF THE ARM, SHOULDER AND HAND (DASH) AND THE UPPER EXTREMITY FUNCTIONAL INDEX (UEFI) IN PATIENTS WITH POSTTRAUMATIC ELBOW STIFFNESS. (2nd June 2020) - Birinci, T.; Kaya Mutlu, E.; Altun, S.
Abstract : Background: There are many patient-rated outcome measures to assess the subjective component of function in musculoskeletal disorders of elbow. The first step of functional assessment is to select the instrument, which is sufficiently responsive. Although the disabilities of the arm, shoulder and hand (DASH) and the upper extremity functional index (UEFI) are widely used in reporting outcomes in upper extremity function, the responsiveness of these two scales has not been investigated in elbow disorders. Objectives: This study aimed to compare and report the responsiveness of the DASH and the UEFI in patients with posttraumatic elbow stiffness. Methods: Fifty-seven patients with posttraumatic elbow stiffness (32 women; mean age, 44.54 ± 6.51 years) were included. All patients completed the DASH and UEFI at baseline and after a six-week intervention, which was a structured exercise program. Patients who improved (much improved and slightly improved) and those who unimproved were defined using a 5-point global rating chance scale (GROC). Responsiveness was assessed using effect size and standardized response mean (SRM). ES has observed the mean change scores divided by the standard deviation of the initial score. SRM was calculated for the improved group and the unimproved group, dividing the mean change scores by the standard deviation of mean change scores. Similar to effect size, SRM values and ES values of 0.20, 0.50 and 0.80 were considered small, moderate or large, respectively. Results: Forty-eight patients (84.21%) were classified improved and 9 patients (15.79%) were classified unimproved according to the GROC. Effect sizes and SRMs were large (greater than 1.00) for participants who were "much improved" or "slightly improved" on the GROC for both the DASH and UEFI. For groups of participants who improved on the GROC, effect sizes and SRMS were ranged from 1.87 to 2.09 and 2.13 to 2.56 for the DASH, and 1.59 to 2.16 and 1.65 to 2.29 for the UEFI, respectively (Table 1 ). Conclusion: These findings showed that for patients receiving physiotherapy for the management of elbow stiffness, both the DASH and the UEFI are similarly responsive to change in symptoms and disability and similarly able to discriminate between patients who improved or unimproved. References: [1]Hudak PL, Amadio PC, Bombardier C. Development of an upper extremity outcome measure: the DASH (disabilities of the arm, shoulder and hand). The Upper Extremity Collaborative Group (UECG). American journal of industrial medicine. 1996;29(6):602-8. [2]Stratford PW, Binkley JM, Stratford DM. Development and initial validation of the upper extremity functional index. Physiotherapy Canada. 2001;53(4):259-67. [3]Smith MV, Calfee RP, Baumgarten KM, Brophy RH, Wright RW. Upper extremity-specific measures of disability and outcomes in orthopaedic surgery. The Journal of bone and joint surgery American volume. 2012;94(3):277-85. Characters from table content including title and footnotes: 783 Disclosure of Interests: None declared